Logika Induktif dan Deduktif Dalam Tradisi Pemikiran USUL AL-FIQH - A. Yasid, A. Yasid (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Logic  occupies  a  central  position  in  the  tradition  of usul al-fiqh thought. Besides referring to the verbal revelation, the formulation  of  the  rules  of  usul al-fiqh is also  based  on  formal logic so that it cannot be easily cracked all along.  The logic with its main attention on the activity of the preparation of the ri ght argument  is  built  to  study  the  various  methods  and  principles used  to  distinguish  the  reasoning  straight  and  distorted  one. Inductive  and  deductive  logic  are  typical  ways  of  working  in  a world  of  usul al-fiqh  thought.  Inductive  logic  is  used  to  draw conclusions  from  individual  cases  that  have  a  range  of  very specific  to  general  conclusions.  Whereas  deductive  logic  is  the opposite way. It?s used to draw conclusions from things that are common  to  the  individual  case.  In  the  tradition  of  usul al-fiqh thinking, inductive logic is often used by Ahnaf  schools. While many of deductive logics are demonstrated by the yurisprudence of Mutakallimin followed by the majority of Islamic Juries.